Can Think Pair Share Assisted by Mind Mapping Affect Students’ Cognitive Learning Outcomes? - Anggraini, Adinda Dwi Setia; Abduh , Muhammad (Jurnal Penelitian dan Pengembangan Pendidikan, 2022)
In the era of globalization, the emergence of learning problems is something that is difficult to avoid, not least in studying the content of social studies lessons. The TPS type cooperative model will be able to maximize student activity in the learning that is carried out. This study aims to analyze the effect of the TPS type cooperative learning model with the help of mind mapping on the acquisition of cognitive learning outcomes for elementary social studies. This research uses a quantitative approach. The research design used a pre-experimental and one group pretest-posttest design. The subjects of this study were 15th grade students who were selected using purposive sampling technique. Research subjects will be given a pretest and posttest. The data from the pretest and posttest were then tested for normality as a prerequisite test for hypothesis testing. In the pretest results, it was found that the average number of students was 53.33 and the posttest increased by 85.77. In the normality test, the significance value of the pretest was 0.179 and the posttest was 0.246, both of which were worth more than 0.05, meaning that the data were normally distributed. Based on the analysis of the hypothesis through the paired sample t-test, a significance value (2-tailed) of 0.000 was obtained, which was less than 0.05. It was concluded that the implementation of the TPS type cooperative learning model with the aid of mind mapping significantly affected the cognitive learning outcomes of elementary social studies.